2022
DOI: 10.1021/acs.iecr.2c03271
|View full text |Cite
|
Sign up to set email alerts
|

Microbubble-Enhanced Bitumen Separation from Tailing Slurries with High Solid Contents

Abstract: Bitumen residues in oil sand tailings ponds create greenhouse gas emissions and threaten the ecosystem. However, it is technically challenging to recover bitumen residues from tailing slurries with high solid contents. This study investigates a novel concept of microbubble-enhanced bitumen recovery during hydrotransport in a laboratory-scale pipeline loop. Our results revealed that bubbles had a positive impact on bitumen recovery. Furthermore, bitumen recovery efficiency increases significantly when the tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…For a large gas flow rate, the efficiency of mechanical shearing in decreasing the mean bubble diameter is weakened owing to the energy dissipation to a larger gas volume [50,51]. In addition, at the higher gas flow rate, bubbles coalesce more at a higher gas fraction [9]. However, the high pressure gradient in the chamber can force the deformation of bubbles and in turn contributes to the breakup of large bubbles [52].…”
Section: Dependence Of Bubble Sizes On Gas Flow Rate Pressure Of the ...mentioning
confidence: 99%
See 2 more Smart Citations
“…For a large gas flow rate, the efficiency of mechanical shearing in decreasing the mean bubble diameter is weakened owing to the energy dissipation to a larger gas volume [50,51]. In addition, at the higher gas flow rate, bubbles coalesce more at a higher gas fraction [9]. However, the high pressure gradient in the chamber can force the deformation of bubbles and in turn contributes to the breakup of large bubbles [52].…”
Section: Dependence Of Bubble Sizes On Gas Flow Rate Pressure Of the ...mentioning
confidence: 99%
“…Recent studies demonstrate that these bubbles have promising potential as separation agents in various industries, such as oil recovery and mineral processing [7,8]. For example, microbubbles greatly improve heavy oil recovery from concentrated slurries [9] and enhance the extraction of organic waste and valuable minerals [10,11]. Moreover, microbubbles have been found to be effective in defouling contaminated surfaces [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, microbubble injection is found to be effective in enhancing bitumen recovery. Bubbles with small sizes (such as nanobubbles) can lead to the attachment of large bubbles onto solid particle surfaces and possibly improve the separation efficiency. , Experimental studies have demonstrated that microbubbles in the slurry flow improve the recovery efficiency of bitumen in a lab-scale pipeline. …”
Section: Introductionmentioning
confidence: 99%
“…Articles included in the present collection include three cover articles: an electrochemical H 2 pump membrane technology (July 2023), 36 a study on the permeability of hydrofluorocarbons (HFCs) in polymer membranes (March 2023), 37 and the recovery of He from natural gas streams using membranes (January 2023). 38 Additional separation-focused articles include the removal of perfluorinated and polyfluorinated substances (PFAS) from H 2 O, 39 a process analytical methodology and development of thermodynamic phase diagram of ternary mixtures of agrochemicals in solvent, 40 a description of membrane test equipment, 41 microbubble-enhanced bitumen separation, 42 and the conversion of CO 2 to dimethyl ether (DME), using a membrane reactor. 43 Thermodynamics, Transport, and Fluid Mechanics is the topic area in I&ECR with the highest rate of participation of industrial authors as a percentage of the articles published.…”
mentioning
confidence: 99%